2018
DOI: 10.1177/2167696818799833
|View full text |Cite
|
Sign up to set email alerts
|

Turning From Parents: Psychological Distancing and Attachment-Related Changes in Regret for Immediate Contact in Emerging Adulthood

Abstract: This longitudinal study examined how emerging adults psychologically distance themselves from parents. Every week during their first semester at college, participants ( n = 71, M age = 18 years [ SD = 0.48]) read hypothetical vignettes describing emotionally salient situations they could encounter at college. Participants then provided information about whether they would regret not being in immediate contact with parents versus peers when dealing with the aftermath of these situations. Results suggested that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 86 publications
0
4
0
Order By: Relevance
“…Emerging adulthood is a time during which most individuals leave the home of their parents, 1 enter college or begin a career, seek romantic relationships, gain financial independence, and make individual decisions on their own (Arnett, 2004; Barlett et al, 2020). As emerging adults become increasingly self-reliant, they continue to individuate themselves from their parents and turn to similarly-aged peers and romantic partners for support and companionship (Dykas & Siskind, 2020). The degree to and means by which individuals experience emerging adulthood through its five defining features can vary by how they gain independence from their parents during this developmental stage, and can significantly impact developmental outcomes (Kavčič & Zupančič, 2019).…”
Section: Individuation and The Defining Features Of Emerging Adulthoo...mentioning
confidence: 99%
“…Emerging adulthood is a time during which most individuals leave the home of their parents, 1 enter college or begin a career, seek romantic relationships, gain financial independence, and make individual decisions on their own (Arnett, 2004; Barlett et al, 2020). As emerging adults become increasingly self-reliant, they continue to individuate themselves from their parents and turn to similarly-aged peers and romantic partners for support and companionship (Dykas & Siskind, 2020). The degree to and means by which individuals experience emerging adulthood through its five defining features can vary by how they gain independence from their parents during this developmental stage, and can significantly impact developmental outcomes (Kavčič & Zupančič, 2019).…”
Section: Individuation and The Defining Features Of Emerging Adulthoo...mentioning
confidence: 99%
“…A recent study (Bohn et al, 2022) of individuals in emerging adulthood also reported that the relationship between attachment to partners and attachment to parents in this period was not strong. Separating psychologically from one’s parents to reorganize attachment hierarchies may be a common developmental process during emerging adulthood (Dykas & Siskind, 2020). Thus, emerging adulthood might be a pivotal period to reorganize attachment representation, which is consistent with Ruble’s phase model of transitions (1994).…”
Section: Discussionmentioning
confidence: 99%
“…The social provision of integration was not significantly related to either caregiver, which suggests that continued attachment does not directly influence students’ view that their parental relationship provides opportunities for social events while attending college. This finding is likely related to emerging adults’ tendency to psychologically distance themselves from their caregivers during the early periods of college (Dykas & Siskind, 2020), as well as to their ability to adjust to college and pursue the task of separation-individuation (Mattanah et al., 2011).…”
Section: Discussionmentioning
confidence: 99%